Numerical study of hybrid systems combining different WECs microarrays based on the TGL semi-submersible floating platform - Li, Mingchen; Wei, Changdong; Li, Lilei; Yuan, Zhenyu; Liu, Yanjun; Xue, Gang (Frontiers in Marine Science, 2025)
In this study, a novel wind-wave energy hybrid concept is proposed, consisting of a Three Gorges Leading semi-submersible floating wind turbine and multiple point absorption wave energy converters (WECs). Based on three-dimensional potential flow theory, numerical simulations are conducted using the hydrodynamic analysis software AQWA. The existing experimental data are used to validate the reliability of the numerical model by comparing and analyzing the hydrodynamic responses of the semi-submersible platform and WECs. Subsequently, the Y-shaped WECs microarray form and the Triangular WECs microarray form are designed based on the different connection methods between WECs and the turbine platform. Numerical simulation is conducted to study the influence of these WECs microarrays on the hybrid system’s performance. The results show that WECs microarray significantly affects the wave contours under short waves. Regarding platform motion stability, the Y-shaped microarray shows superior performance. Regarding mooring line tension, the hybrid system has an advantage under short waves. Regarding absorbed power, multi-body hydrodynamic interactions significantly enhance the WECs’ power absorption capacity. Overall, this study will contribute to the design of wind-wave energy hybrid systems.